Modulatory effect of Decalepis hamiltonii on ethanol-induced toxicity in transgenic Drosophila model of Parkinson's disease. - Jahromi, S.R.; Haddadi, M.; Shivanandappa, T.; Ramesh, S.R. (Neurochemistry International, 2015)
Overexpression of human ?-synuclein gene in Drosophila can reduce lifespan, and we have performed lifespan assay for A30P and A53T?-synuclein transgenic and control (elav-GAL4, UAS-A30P, UAS-A53T) flies. Our results showed reduced lifespan of transgenic flies compared to controls. We have also investigated behavioral responses, levels of reactive oxygen species (ROS) and lipid peroxidation (LPO) and activities of catalase (CAT) and superoxide dismutase (SOD) in a combined genetic-toxin model (Ethanol-A30P or A53T?-synuclein models) and controls. Our results showed that sedation time (ST50) of A30P or A53T?-synuclein PD model flies was significantly lower while recovery time (RC50) of them was remarkably higher compared to control flies. The levels of oxidative markers (ROS and LPO) were significantly higher and the activities of CAT and SOD were lower in transgenic flies that underwent ethanol exposure compared to control. Based on our earlier studies on antioxidant properties of isolated and characterized molecules from Decalepis hamiltonii (Dh) root extract, its protective effect in this combined toxicity model has been investigated. Surprisingly, Dh treatment increased ST50 and decreased RC50 values of transgenic flies. Moreover, we showed that Dh pre-treatment could decrease the levels of ROS and LPO and increase the activities of CAT and SOD in the ethanol-?-synuclein model. This is the first report on protective effects of natural antioxidants in A30P or A53T?-synuclein PD model flies against oxidative stress induced by ethanol.